Effect of intracuff dexamethasone on incidence and severity of post operative sore -Prospective randomized study - Sunil Rajan; Naina Narayani; Jerry Paul; Lakshmi Kumar (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Postoperative sore throat (POST) continues to be a common concern following endotracheal intubation. Objectives of the present study were to compare the effects of intracuff dexamethasone on the incidence and severity of POST, postoperative hoarseness of voice (POHV) and cough (POC). Material and Methods: This prospective, randomized, double blinded study was conducted in 60 patients undergoing short laparoscopic surgery lasting <2 h. Patients were randomly allocated into Group A and B. After intubation, endotracheal tube (ETT) cuffs were filled with saline in group A and with 0.1 mg/kg dexamethasone in group B. All patients received general anesthesia as per a standardized protocol. Incidence and severity of POST, POC, and POHV were assessed. Results: As compared to group A, the number of patients who had sore throat was significantly low in group B at 2, 6, 12, and 24 h (P < 0.001). Though more number of patients in group A had postop cough at all time points and postop hoarseness of voice at 2,6, and 12 h, the difference was statistically significant only at 2 h and 6 h for both. Severity as well as the incidence of POST, POC, and POHV showed a downward trend in both groups with time. In group B, no patient had POST after 12 h, POC after 6 h, and none complained of POHV in the postoperative period. Conclusion: Intracuff dexamethasone 0.1 mg/kg significantly reduces incidence and severity of POST, POC, and POHV which occur following general anesthesia with endotracheal intubation in patients undergoing short pelvic laparoscopic procedures lasting <2 h.